2009
DOI: 10.1587/transinf.e92.d.1847
|View full text |Cite
|
Sign up to set email alerts
|

Handover Management for VoWLAN Based on Estimation of AP Queue Length and Frame Retries

Abstract: SUMMARYSwitching a communication path from one Access Point (AP) to another in inter-domain WLANs is a critical challenge for delaysensitive applications such as Voice over IP (VoIP) because communication quality during handover (HO) is more likely to be deteriorated. To maintain VoIP quality during HO, we need to solve many problems. In particular, in bi-directional communication such as VoIP, an AP becomes a bottleneck with the increase of VoIP calls. As a result, packets queued in the AP buffer may experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…As an RTS frame is always transmitted at the lowest rate (e.g., 6 Mb/s in 802.11a/g and 1 Mb/s in 802.11b), an MN can appropriately detect the change of wireless link quality. In our previous study [8], we found that an RTS retry ratio of less than 0.6 satisfies adequate VoIP call quality, and we suggest it as a threshold value for initiating HO in this study.…”
Section: Frame Retriessupporting
confidence: 57%
See 1 more Smart Citation
“…As an RTS frame is always transmitted at the lowest rate (e.g., 6 Mb/s in 802.11a/g and 1 Mb/s in 802.11b), an MN can appropriately detect the change of wireless link quality. In our previous study [8], we found that an RTS retry ratio of less than 0.6 satisfies adequate VoIP call quality, and we suggest it as a threshold value for initiating HO in this study.…”
Section: Frame Retriessupporting
confidence: 57%
“…That is, VoIP packets to MNs are liable to experience large queuing delay or packet loss due to increase in queue length or buffer overflow in the AP buffer because each MN and AP has almost the same priority level of frame transmission by following the CSMA/CA scheme. In our previous study [8], we found that Request-to-Send (RTS) frame retries and Round-Trip Time (RTT) between MN and AP can be potential MN-initiated HO triggers for 802.11g. We briefly describe these triggers in the following subsections.…”
Section: Handover Triggers For 80211mentioning
confidence: 99%
“…The MNs implement the VoIP call with the CN. The new NHM working in a multi-homing is similar to [39][40] with respect to improve the VoIP session conservation among the MN and CN, it must be correctly switched among the single-casting and bi-casting modes in reply to wireless network rules. Single-casting mode known as the MN communicates with a CN using only one IF.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results indicate that the AP's queue length has a large impact on VoIP communication quality, how can MSs detect the increase in the AP's queue length without modifying an AP? We then proposed estimating the AP's queue length based on the RTT between an MS and an AP (Niswar et al, 2009a). Note that in this chapter the RTT between the MS and the AP is called Wireless RTT (WiRTT).…”
Section: Handover Triggers For Multi-rate and Congested Wlansmentioning
confidence: 99%
“…We then proposed an extended handover management method based on these triggers (Niswar et al, 2009a). To support soft handover on an end-to-end basis, the handover management method also supports multi-homing, cross-layer architectures, a multi-path transmission function, and a handover manager (HM) similar to the previous method .…”
Section: Handover Management For Multi-rate and Congested Wlansmentioning
confidence: 99%